2004
DOI: 10.1086/425098
|View full text |Cite
|
Sign up to set email alerts
|

The Starbucks Brandscape and Consumers’ (Anticorporate) Experiences of Glocalization

Abstract: Prior studies strongly suggest that the intersection of global brands and local cultures produces cultural heterogeneity. Little research has investigated the ways in which global brands structure these expressions of cultural heterogeneity and consumers' corresponding experiences of glocalization. To redress this gap, we develop the construct of the hegemonic brandscape. We use this theoretical lens to explicate the hegemonic influence that Starbucks exerts upon the sociocultural milieus of local coffee shops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
486
1
20

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 576 publications
(516 citation statements)
references
References 29 publications
9
486
1
20
Order By: Relevance
“…Brands and the managers who design them play an important role in changing culture (Nixon 2003;Ritzer 1993;Thompson and Arsel 2004). We extend this stream of research on cultural change by showing how managers can get brands to function as symbolic devices, helping to create transnational imagined worlds, such as the imagined Asia we have described.…”
Section: Discussion: Brands As Symbolic Formsmentioning
confidence: 81%
See 3 more Smart Citations
“…Brands and the managers who design them play an important role in changing culture (Nixon 2003;Ritzer 1993;Thompson and Arsel 2004). We extend this stream of research on cultural change by showing how managers can get brands to function as symbolic devices, helping to create transnational imagined worlds, such as the imagined Asia we have described.…”
Section: Discussion: Brands As Symbolic Formsmentioning
confidence: 81%
“…We ground our study in the burgeoning literature on the symbolic dimension of brands (Holt 2002;McCracken 2005;Ritzer 1993;Schroeder and Salzer-Morling 2006;Sherry 2003;Thompson and Arsel 2004). This stream of research has shown that brand stories increasingly frame the way we view a globalizing world and its contradictions.…”
Section: The Role Of Brands In the Global Marketplacementioning
confidence: 99%
See 2 more Smart Citations
“…Although it is possible to think of the answer to this question as being something that can be left to empirical adjudication on a study-bystudy basis, field theory suggests that a more systematic and generalizable formulation is feasible. Recent research suggests that across a wide variety of products and industries, the type of audience that is attracted to appeal of ''authenticity,'' ''originality,'' and ''craft'' values is essentially the same: young, highly educated members of symbol and culture production occupations (Bourdieu, 1984;Holt, 1998Holt, , 2002Johnston & Baumann, 2007;Thompson & Arsel, 2004).…”
Section: Audiences and Producers One Space Or Two?mentioning
confidence: 99%